Schistura tenebrosa, a new species of loach from the Kwai Noi River system, Mae Khlong basin, Thailand (Teleostei: Nemacheilidae) - Kangrang, Punnatut; Page, Lawrence M.; Beamish, F. William H. (Zootaxa, 2012)
A new species of Schistura is described from the Kwai Noi, Mae Khlong basin, in the Thong Pha Phum District ofKanchanaburi Province in western Thailand. The species is distinguished from all other species of Schistura by a uniformdusky brown color pattern without marks on the dorsum or side of body and with many conspicuous supplementaryneuromasts along the lateral line and on the head. It is further distinguished from other species of Schistura lacking markson the body by its dark brown color, an incomplete lateral line extending only to beneath the dorsal fin, and the origin ofthe dorsal fin located above the origin of the pelvic fin. The species is small, reaching only 46.0 mm SL, 55.1 mm TL, and inhabits shallow gravel and rubble riffles in small streams.